Analysis of Video Assistant Referee (VAR) Technology Effectiveness in Correcting and Supporting Decisive Refereeing Decisions in the Iraqi Stars Football League 2024/2025 Season - Ahmed Jalal Ibrahim; Ali Sabah Adday; Ali Hussein (Journal of Education and Sport Science, 2026)
Objectives: This study aimed to analyze the effectiveness of Video Assistant Referee (VAR) technology in correcting and supporting decisive refereeing decisions in the Iraqi Stars Football League during the 2024/2025 season. Materials and Methods: This study used a descriptive analytical method. The research population consisted of 28 referees accredited by the Iraqi Football Association and licensed to officiate matches using VAR technology. The sample included 280 decisive refereeing cases reviewed through VAR intervention, including penalty kicks, red cards, goals, mistaken identity, and other discretionary cases. Data were collected through official referee reports, VAR analysis forms, and official match video recordings. Data were analyzed using percentages, mean, standard deviation, Pearson correlation coefficient, and Chi-square test with SPSS version 22. Results: The findings showed that VAR contributed significantly to correcting decisive refereeing decisions. Of the 280 cases reviewed, 75% resulted in decision changes, while 25% confirmed the original decision. Penalty kicks represented the highest proportion of VAR interventions at 36.4%, followed by other discretionary cases at 24.6%, red cards at 20.7%, goals at 17.9%, and mistaken identity at 0.4%. The Chi-square test indicated a significant relationship between decision type and review outcome. Conclusions: VAR technology proved effective in supporting referees and improving the accuracy of decisive decisions in the Iraqi Stars Football League. The greatest impact was found in penalty kick and red-card decisions. The study recommends continued implementation of VAR, stronger referee training, and improved stadium technology infrastructure.